Más et ses « marqueurs du standard » en espagnol : de ~ que. - Marine Poirier (Corela)
The question of the distribution de / que as « standard markers » is debated in the literature on comparison in Spanish. In this study, we examine this question in the light of an interlocutive chronosyntax approach, which studies the contribution of signifiers to the dynamics of sense-making by the effets they produce on the interprent at the moment of their occurrence. We propose de and que operate differently in the «receptive framework» of interlocution, and we then show how this receptive framework functions in the various discourse meanings that grammars identify for más de and más que.